ПЕДАГОГИК ФАОЛИЯТДА ЎҚИТУВЧИНИНГ ЎЗ УСТИДА ИШЛАШ ФАОЛИЯТИНИ ШАКЛЛАНТИРИШНИНГ ИЖТИМОИЙ-ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Шакарбоева, Ш.А. (SCIENCE and SOCIETY, 2024)
This article is devoted to the topic of Socio-psychological problems of raising children in the conditions of pedagogical activity. Thus, Mao Zedong’s pedagogical activity is based on such issues as psychological foundations, social psychological determinants, psychological motives, tolerance and empathic motives.